Radial head arthroplasty vs. open reduction and internal fixation in Mason 3 radial head fractures: meta-analysis of prospective trials - Domenico De Mauro, MD; Sami Abou Chakra; Francesco Liuzza, MD; Amarildo Smakaj, MD; Giuseppe Rovere, MD, PhD; Giulio Maccauro, MD; Omar El Ezzo, MD (JSES International)
Background: Radial head fractures (RHF) represent about one-third of all elbow fractures, comprising approximately 2%-5% of all fractures sustained. The aims of this systematic review and meta-analysis are as follows: (i) to compare complications rate in patients undergoing radial head arthroplasty (RHA) or open reduction and internal fixation as surgical treatments for Mason type 3 RHF; (ii) to compare clinical outcome and functional score in patients undergoing RHA or ORIF in Mason type 3 RHF. Methods: Following the preferred reporting items for systematic reviews and meta-analyses guidelines, a comprehensive literature systematic review of literature was conducted up to March 2024. All prospective studies were included. The analysis employed the log odds ratio (OR) and 95% confidence interval (CI) as the outcome measure. Results: Six studies were incorporated into the systematic review. A total of three studies, published between 2009 and 2021, were included in the meta-analysis. A cohort of 169 patients affected by Mason 3 RHFs was collected. The ORIF group included 65 patients, and 26 events of complications after ORIF were observed. RHA group, instead, consisted of 70 patients, and 8 events of complications were identified. Conclusion: Our findings reveal that the Mason type 3 RHFs treated with open reduction and internal fixation, exhibits a higher risk of complications compared to those patients treated with RHA. Moreover, the standardized mean difference analysis suggests that the ORIF group demonstrates a lower mean Broberg and Morrey Elbow score in comparison to the RHA group, with a higher functional recovery in RHA group.